The Relationship Between Adherence To Antidiabetic Treatment and Hba1c Values In Type 2 Diabetes Mellitus Patients At Royal Prima Hospital, Medan, In 2025 - Azijah Hafni Lubis; Elviyanti Elviyanti; Boyke Boyke (International Journal of Health and Pharmaceutical (IJHP), 2025)
Type 2 diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia from inadequate insulin synthesis or insulin resistance. Medication adherence significantly impacts glycemic control measured by HbA1C levels. This study examined the relationship between antidiabetic medication adherence and HbA1C levels in type 2 diabetes patients. This analytical cross-sectional study enrolled 77 outpatients at Royal Prima General Hospital, Medan. The Morisky Medication Adherence Scale (MMAS-8) questionnaire assessed adherence, while HbA1C levels were extracted from medical records. Chi-square analysis (p less than 0.05) and odds ratio calculations were performed using IBM SPSS Statistics. Results demonstrated that 77.9% of patients exhibited uncontrolled HbA1C levels above 7%, with 76.6% showing moderate to low medication adherence. Statistical analysis revealed a highly significant association (χ² = 17.661, p = 0.003, OR = 11.621), with patients demonstrating low adherence experiencing 11.621-fold increased odds of uncontrolled HbA1C. Notably, zero patients with low adherence achieved adequate glycemic control. The study concludes that medication adherence represents a critical modifiable determinant of glycemic control. Systematic adherence screening, targeted barrier-specific interventions including medication reminders and patient education, and enhanced provider communication should be integrated into routine diabetes management to optimize glycemic control and reduce diabetes-related complications.